CONFIRMATORY FACTOR ANALYSIS OF LATENT SUB-SCALES OF TEACHER RESEARCH ENGAGEMENT OF PUBLIC SCHOOLS ELEMENTARY TEACHERS - Langam, H L (PEOPLE: International Journal of Social Sciences, 2019)
The current study aims to find the pattern of relationship and establish factorial validity among predictors of teacher research engagement. This study employed a descriptive- correlational research design. A validated researcher-made Teacher Research Engagement Survey with three subscales was used to gather data from 612 public school teachers. The researcher then computed descriptive statistics and conducted a confirmatory factor analysis of the hypothesized measurement model and a modified measurement model. The analysis revealed that teachers have high physical research engagement with (x̄=3.1149, SD=0.85429), high cognitive research engagement with (x̄=3.7145, SD=0.9505) and fair emotional research engagement with (x̄=3.4513, SD=0.8463). The correlation matrix presents that there is a strong positive highly significant relationship between physical research engagement and cognitive research engagement(r=0.632, p>0.05), physical research engagement and emotional research engagement (r=0.705, p>0.05), and cognitive research engagement and emotional research engagement (r=0.830, p>0.05). The modified measurement model of teacher research engagement obtained acceptable and better model fit indices of CMIN/DF=3.939, CFI = 0.972, SRMR = 0.054, RMSEA = 0.069, NNFI/TLI = 0.955, GFI) = 0.945 and PClose = 0.000. This study concludes that teachers have high physical research engagement, and high cognitive research engagement, and fair emotional research engagement. There is a significant relationship among physical research engagement, cognitive research engagement, and emotional research engagement subscales. In the confirmatory factor analysis, the modified model was able to obtain a better model fit indices, factor loadings, and covariance.